Clinically detectable structural abnormalities in pediatric‐onset multiple sclerosis: A large‐scale magnetic resonance imaging analysis. Issue 2 (29th January 2021) - Levman, Jacob; Das, Avilash; MacDonald, Allissa; MacDonald, Patrick; Berrigan, Lindsay; Takahashi, Emi
Abstract: Background: Multiple Sclerosis is characterized by neural demyelination. Structural magnetic resonance imaging (MRI) provides soft tissue contrast, which forms the basis of techniques for extracting regional biomarkers across a participant's brain. Objectives: To investigate the clinical presentation of multiple sclerosis in a large‐scale MRI analysis that includes thorough consideration of extractable structural measurements (average and variability of regional cortical thicknesses, cortical surface measurements, and volumes). Methods: We performed a large‐scale retrospective analysis of 370 T1 structural volumetric MRIs from 64 participants with multiple sclerosis and compared them with a large cohort of neurotypical participants, consisting of 993 MRIs from 988 participants. Regionally distributed measurements of cortical thickness (average and standard deviation) were extracted along with surface area, surface curvature, and volumetric measurements. Results: The largest observed finding involved regionally distributed reductions in average cortical thickness, with the parahippocampal region exhibiting the largest effect size, a finding that may be linked with known hippocampal atrophy in multiple sclerosis. Group‐wise differences were also observed in terms of distributed volume, surface area, and surface curvature measurements. Conclusions: Participants with pediatric‐onset multiple sclerosis present clinically with a variety of structural abnormalities, including perirhinal cortex thickness abnormalities not previously reported in the literature. Abstract : We performed a large‐scale retrospective analysis of 370 T1 structural volumetric magnetic resonance imaging examinations (MRIs) from 64 participants with multiple sclerosis (MS) and compared them with a large cohort of neurotypical participants, consisting of 993 MRIs from 988 participants. Regionally distributed measurements of cortical thickness (average and standard deviation) were extracted along with surface area, surface curvature, and volumetric measurements. Group‐wise differences were observed in terms of distributed volume, surface area, and surface curvature measurements in the parahippocampal region, as well as abnormalities of perirhinal cortex thickness not previously reported in the literature.